Indonesia’s fast attack craft acquisition : toward a “balanced” fleet? - Ristian Atriandi Supriyanto (2012)
The Indonesian Navy recently received its second locally-made fast attack craft with a plan to procure 14 units until 2014. This is part and parcel of its plan to have a ‘balanced’ fleet capable of performing wide-ranging naval tasks.